The Mediating Effect of Waiting Time on the Relationship Between Service Quality and Customer Satisfaction - Impira, Alim (2012)
The service delivery system of the public sector has been under constant criticisms from members of the public due to its inefficiency. Hence, the Malaysian government has implemented various administrative measures to upgrade the service delivery system of the public sector. One of the most important determinants contributing to satisfaction in the service delivery system is service quality. The objective of this study is to examine the relationship between service quality and customer satisfaction and determine the mediating effect of waiting time on the relationship.The study was conducted in the Royal Malaysian Customs Department (RMCD). Questionnaire was administered to 405 respondents, who were Customs agents. However, only 321 responses were received and the final data of 297 responses were used for analysis. Data were analyzed using SPSS Version 19.00 and structural equation modeling (SEM) by means of the “Analysis of Moment Structures” (AMOS 19.0). The findings indicate that service quality has a direct significant influence on customer satisfaction. The result also shows that responsiveness was rated as the most dominant dimension of service quality to influence customer satisfaction, followed by assurance, tangibles, empathy, and reliability. This study confirms that waiting time has a significant mediating effect on the relationship between service quality and customer satisfaction. The fundamental contribution of the study is the formulation of a structural model that can be used to understand the interaction between service quality, waiting time, and customer satisfaction. The model derived from this study can be used as a tool to improve customer satisfaction. Hence, based on the findings of this study, RMCD should emphasize the attributes of service quality to ensure customer satisfaction with the services they provide. Most importantly, RMCD should focus on reducing waiting time to receive service in order to enhance the service delivery system of the department. Recommendations for future studies and limitations of the present study are also discussed.